2007
DOI: 10.1261/rna.768207
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of targeting by endogenous and exogenous microRNAs and siRNAs

Abstract: Vertebrate mRNAs are frequently targeted for post-transcriptional repression by microRNAs (miRNAs) through mechanisms involving pairing of 39 UTR seed matches to bases at the 59 end of miRNAs. Through analysis of expression array data following miRNA or siRNA overexpression or inhibition, we found that mRNA fold change increases multiplicatively (i.e., log-additively) with seed match count and that a single 8 mer seed match mediates down-regulation comparable to two 7 mer seed matches. We identified several ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
336
3
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 359 publications
(363 citation statements)
references
References 61 publications
23
336
3
1
Order By: Relevance
“…Comparison of mRNAs downregulated by miR-124 and miR-124-UU21 showed surprisingly limited overlap between mRNAs regulated by each miRNA. Seed sequences complementary to the transfected miRNA were enriched in each set of downregulated mRNAs, consistent with previous studies on miR-124 [41,42,80]. In addition, we found that seed sequences in which the 5' terminal base of miR-124 is not complementary to the seed sequence were enriched in mRNAs regulated specifically by miR-124, while seeds with different patterns of complimentarity were enriched in mRNAs regulated specifically by miR-124-UU21, or by both miRNAs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparison of mRNAs downregulated by miR-124 and miR-124-UU21 showed surprisingly limited overlap between mRNAs regulated by each miRNA. Seed sequences complementary to the transfected miRNA were enriched in each set of downregulated mRNAs, consistent with previous studies on miR-124 [41,42,80]. In addition, we found that seed sequences in which the 5' terminal base of miR-124 is not complementary to the seed sequence were enriched in mRNAs regulated specifically by miR-124, while seeds with different patterns of complimentarity were enriched in mRNAs regulated specifically by miR-124-UU21, or by both miRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…Since target sites in the Itgb1 3' UTR could be regulated by miR-124, but not miR-124-UU21, we expected that different seed sequences would be present in the 3' UTRs in the three sets of genes downregulated at the mRNA level by miR-124, miR-124-UU21, or both miRNAs in P19 cells [41,42,80]. We searched the 3' UTRs of mouse genes in the UTRdb database [59] for six different seed sequences partially or completely complementary to the 5' end of miR-124, miR-124-UU21, or both miRNAs (Supplemental Fig.…”
Section: Mir-124 and Mir-124-uu21 Regulate Distinct Sets Of Genes In mentioning
confidence: 99%
“…Results for all 10 bins were then combined to represent the aggregate signal and background for this site (large plot). (Grimson et al 2007;Nielsen et al 2007), away from the centers of long UTRs (Gaidatzis et al 2007;Grimson et al 2007;Majoros and Ohler 2007), and near to nucleotides that can pair to miRNA nucleotides 13-16 (Grimson et al 2007).Comparative analysis has also revealed the wide scope of metazoan miRNA targeting, indicating that many genes of mammals, flies, and worms are miRNA targets Krek et al 2005;Lewis et al 2005;Xie et al 2005;Lall et al 2006). For example, combining the 3ЈUTR conservation attributed to miRNA seed matching with that from ORFs indicates that over one third of human protein-coding genes have been under selective pressure to maintain pairing to miRNAs .…”
mentioning
confidence: 99%
“…We use the term "background" instead of "noise" because the latter term may connote variance in the background estimate as opposed to the estimate itself. The number of sites conserved above background reflects the sensitivity of the analysis, whereas the ratio of signal to background reflects its specificity.We first considered the three 7-8mer seed-match types (8mer, 7mer-m8, 7mer-A1), which correlate most strongly with targeting efficacy (Grimson et al 2007;Nielsen et al 2007) and are among the miRNA matches currently used to predict conserved targets of metazoan miRNAs ( Fig. 2B Ruby et al 2006Ruby et al , 2007Gaidatzis et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation